2019
DOI: 10.3389/fmars.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche Modeling of Three Species of Stenella Dolphins in the Caribbean Basin, With Application to the Seaflower Biosphere Reserve

Abstract: Dolphins of the genus Stenella occur in pelagic waters of both tropical and warmtemperate oceans. Three species, the Atlantic spotted dolphin (Stenella frontalis), the pantropical spotted dolphin (S. attenuata), and the spinner dolphin (S. longirostris) are abundant worldwide, but in the Caribbean Basin they have been poorly studied and information on their distribution patterns is scarce. Specifically, in Colombia's remote Seaflower Biosphere Reserve (SFBR) S. attenuata has been reported occasionally, but S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 62 publications
(97 reference statements)
2
24
0
3
Order By: Relevance
“…From July to December, there is no upwelling because the direction of the trade winds changes and the rain falls, so this period is coined the "wet season" (Invemar and Corpoguajira, 2012). Due to this coastal upwelling, variation in nutrient supply and thus in productivity may affect foraging sources and their availability for juvenile turtles (Arévalo-Martínez and Franco-Herrera, 2008;Paramo et al, 2011), as has been reported for other marine vertebrates such as dolphins (e.g., Farías-Curtidor et al, 2017;Barragán-Barrera et al, 2019). C. mydas feeds on seagrasses and marine macroalgae primarily but also on small marine invertebrates (Bjorndal, 1980;Mortimer, 1981;Seminoff et al, 2002;Makowski et al, 2006;Amorocho and Reina, 2007;Shimada et al, 2014).…”
Section: Study Area and Seasonmentioning
confidence: 96%
See 1 more Smart Citation
“…From July to December, there is no upwelling because the direction of the trade winds changes and the rain falls, so this period is coined the "wet season" (Invemar and Corpoguajira, 2012). Due to this coastal upwelling, variation in nutrient supply and thus in productivity may affect foraging sources and their availability for juvenile turtles (Arévalo-Martínez and Franco-Herrera, 2008;Paramo et al, 2011), as has been reported for other marine vertebrates such as dolphins (e.g., Farías-Curtidor et al, 2017;Barragán-Barrera et al, 2019). C. mydas feeds on seagrasses and marine macroalgae primarily but also on small marine invertebrates (Bjorndal, 1980;Mortimer, 1981;Seminoff et al, 2002;Makowski et al, 2006;Amorocho and Reina, 2007;Shimada et al, 2014).…”
Section: Study Area and Seasonmentioning
confidence: 96%
“…The high connectivity and diversity of C. mydas found in the northern portion of Colombia points to its relevance as a transit feeding area for multiple populations (Arthur et al, 2008). Indeed, previous studies have suggested La Guajira as an important transit area for other marine vertebrates in the Caribbean Sea, like dolphins (Farías-Curtidor et al, 2017;Barragán-Barrera et al, 2019). The dispersal mechanisms by which multiple C. mydas populations can contribute to the observed mixed stock diversity in Colombia are unknown.…”
Section: Atlantic C Mydas Fgs Oceanography and Connectivitymentioning
confidence: 99%
“…The differences in the distribution patterns among Stenella species have been related not only to oceanographic conditions ( do Amaral et al., 2015 ), but also to prey distribution and feeding preferences ( Davis et al., 2005 ). However, in the Caribbean, dolphins of the genus Stenella did not show the same levels of niche partitioning, probably due to the low productivity levels in the Caribbean Sea ( Barragán-Barrera et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its distribution is associated with arid environments with scarce and unpredictable precipitation throughout the year (Muñoz, 1973). However, years with higher rainfall during the winter promote the productivity and development of this and other plant species in an event known as "desert bloom" (Errázuriz and Hanisch, 1995;Chávez et al, 2019). This species is classified as endangered (MINSEGPRES, 2008), which is partially due to its narrow distribution (Cereceda, et al, 2000).…”
Section: Modelo De Distribución Potencial De Leontochir Ovallei Con Dmentioning
confidence: 99%
“…Research suggests that predictions derived from habitat suitability cartography for narrow distribution species is a useful tool for understanding the contribution of different environmental factors to the spatial distribution of species (Franklin, 2010;Urbina-Cardona and Flores-Villela, 2010;Marini et al, 2010;Morales, 2012;Hawk, 2017;Tang et al, 2018;Thapa et al, 2018;Barragán-Barrera et al, 2019;Sarma et al, 2018;Giannakopoulos et al, 2019). Consequently, Wang et al (2012) recommend using predictive models to evaluate the distribution pattern of species with scarce available data.…”
Section: Modelo De Distribución Potencial De Leontochir Ovallei Con Dmentioning
confidence: 99%